Evaluación del potencial de la producción de metano a partir de aguas residuales provenientes de la industria láctea. (2024)
This paper investigates the potential of anaerobic digestion for the treatment of wastewater from the dairy industry, a sector with a high volume of organic-rich waste. A comprehensive analysis of the process is carried out, exploring the composition of the wastewater, conventional treatment methods and the advantages of anaerobic digestion. The stages of anaerobic digestion are explored: hydrolysis, acidogenesis, acetogenesis and methanogenesis, describing the microbial groups and the factors that affect their efficiency (temperature, pH, C/N ratio, organic load, retention time). Different types of biodigesters are compared: AFBR, UASB, ASBR and CSTR, evaluating their characteristics and applicability to the treatment of dairy waste. A mathematical model based on the ADM1 model is implemented to simulate the dynamics of the process and predict methane production. Key factors that affect the efficiency of the process are identified, including ammonia inhibition, pH and VFA concentration.